2008
DOI: 10.1364/oe.16.003130
|View full text |Cite
|
Sign up to set email alerts
|

Normal dispersion erbium-doped fiber laser with pulse energies above 10 nJ

Abstract: We report on an erbium-doped fiber oscillator mode-locked by nonlinear polarization evolution operating in the large normal dispersion regime. The setup produced highly chirped 10 nJ pulses at 37 MHz which can be compressed externally to below 75 fs. Hence, this simple and practical setup is capable of providing ultrashort pulses with a peak power of 140 kW. The pulse formation is indeed subject to intrapulse Raman-scattering but a clean and stable pulse train can be observed. The similarities as well as the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…For instance, the pulse energy generated with 980-nm laser diodes (LDs) [25] is three times lower than that reported with 1480-nm LDs in a similar scheme [26], 3.5 nJ and 10 nJ respectively.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…For instance, the pulse energy generated with 980-nm laser diodes (LDs) [25] is three times lower than that reported with 1480-nm LDs in a similar scheme [26], 3.5 nJ and 10 nJ respectively.…”
mentioning
confidence: 84%
“…This combination of the pulse parameters represents the shortest duration and the high- est energy pulses generated so far in all-fiber Erbium oscillators, at least in publications containing necessary pulse characterisation (interferometric autocorrelation traces, radio-frequency (RF) beat signal etc.). Schemes with NPE mode-locking realized with bulk optics elements provide much better combination of the pulse parameters [24][25][26], specifically 10 nJ, 75 fs.…”
mentioning
confidence: 99%
“…Note, that 1480 nm-pump is likely to give some additional benefits in comparison with 980 nm-pump. For instance, the energy of pulses generated with 980 nm-pump is three times lower [17] than that obtained in a similar scheme with 1480 nm-pump (3.5 nJ against 10 nJ) [18].…”
Section: Introductionmentioning
confidence: 67%
“…In 2007, Chong et al demonstrated Yb-doped fiber lasers with pulse energies above 20 nJ, and dechirped pulse peak powers of nearly 100 kW [18]. In 2008, Ruehl et al reported an erbium-doped fiber oscillator mode-locked by nonlinear polarization evolution operating in the large normal dispersion regime, and producing highly chirped, ultrashort 10 nJ pulses with dechirped peak powers of 140 kW [19].…”
Section: Introductionmentioning
confidence: 99%